2017
DOI: 10.1159/000485092
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes after Surgery for Appendiceal Mucinous Tumours

Abstract: Background: Appendiceal mucinous tumour (AMT) is a very uncommon disease. We aimed to evaluate preoperative and postoperative characteristics as well as long-term outcomes of patients with appendiceal mucinous adenomas and peritoneal pseudomyxoma (PMP). Methods: A consecutive cohort of patients diagnosed with AMT were included in the study. Tumour recurrence and the development of PMP was diagnosed based on the patients' complaints, physical examination, imaging studies, and biopsy results. The calculation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…There is no consensus on the optimal treatment of appendiceal mucocele regarding the type and approach of surgery. Appendicectomy and right hemicolectomy have been proposed for cases of an unruptured appendix, while Cytoreductive Surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) are proposed in ruptured cases with PMP [ 24 ]. A laparoscopic approach is considered to increase the risk of intraoperative rupture and mucus spread [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus on the optimal treatment of appendiceal mucocele regarding the type and approach of surgery. Appendicectomy and right hemicolectomy have been proposed for cases of an unruptured appendix, while Cytoreductive Surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) are proposed in ruptured cases with PMP [ 24 ]. A laparoscopic approach is considered to increase the risk of intraoperative rupture and mucus spread [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appendicectomy and right hemicolectomy have been proposed for cases of an unruptured appendix, while Cytoreductive Surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) are proposed in ruptured cases with PMP [ 24 ]. A laparoscopic approach is considered to increase the risk of intraoperative rupture and mucus spread [ 24 , 25 ]. Overall, the 5-year recurrence rate of LAMN has been estimated at 54% following CRS/HIPEC, compared with other epithelial pathologies and given that low-intensity surveillance is recommended [ 23 , 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, ANMA patients suffer significantly poor prognosis than their AMA counterparts. Multiple studies have reported on advances in AMA treatment (24)(25)(26). Currently, CRS and hyperthermic intraperitoneal chemotherapy (HIPEC) have been shown to offer best treatment for AMA (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, high-grade tumors benefit from debulking surgery and HIPEC, with or without preoperative chemotherapy. 5,12…”
Section: Discussionmentioning
confidence: 99%